Unique characteristics of the novel-GTAW process for the butt joint of ultra-thin silicon steel sheets - Ngo, Manh Huu; Le, Van Thao; Gandham, Bharat; Nguyen, Van Anh; Le, Duy Han; Van, Truong Nguyen; Van, Tuan Nguyen (Elsevier, 2023)
Butt joining of ultra-thin silicon steel sheets is a major challenge because of the ultra-thin thickness, high silicon content, and the coating layer on their surfaces. For the first time, welding butt-joint of the 0.2 mm ultra-thin silicon steel sheets has been performed successfully and reported in this paper. The results show that the weld beads fabricated by the novel-GTAW process are straight, stable, and without defects. They have a narrower width on the top and a larger width on the bottom side compared to the conventional-GTAW process. The mechanical properties of the welding joints also overmatch that of the base metal, confirming good qualities of the weldment. The success of the novel GTAW process in butt weld of ultra-thin silicon steel sheets is because of its unique characteristics: First, the mechanism of the novel-GTAW torch allows removing and blowing the insulation coating layer to prevent its penetration into the melting point and its accumulation on the electrode during the welding process; thus, eliminating welding defects and electrode wear and maintaining the arc stability. Second, the novel-GTAW process enables superiorly reducing the heat input and increasing the cooling rate, which ensures the high quality of the butt weld of ultra-thin silicon steel sheets. Lastly, the shielding efficiency of the melting pool is enhanced to prevent silicon oxidation and welding defects.
Keywords: Novel-GTAW process; Unique characteristics; Butt joint; Ultra-thin sheet; Silicon steel